Effects of increasing temperature and, CO2 on quality of litter, shredders, and microorganisms in Amazonian aquatic systems - Martins, Renato Tavares; Rezende, Renan S.; Gonçalves, José Francisco Júnior; Lopes, Aline; Piedade, Maria Teresa Fernandez; Cavalcante, Heloide de Lima; Hamada, Neusa (PLoS ONE, 2017)
Climate change may affect the chemical composition of riparian leaf litter and, aquatic organisms and, consequently, leaf breakdown. We evaluated the effects of different scenarios combining increased temperature and carbon dioxide (CO2) on leaf detritus of Hevea spruceana (Benth) Müll. and decomposers (insect shredders and microorganisms). We hypothesized that simulated climate change (warming and elevated CO2) would: i) decrease leaf-litter quality, ii) decrease survival and leaf breakdown by shredders, and iii) increase microbial leaf breakdown and fungal biomass. We performed the experiment in four microcosm chambers that simulated air temperature and CO2 changes in relation to a real-time control tracking current conditions in Manaus, Amazonas, Brazil. The experiment lasted seven days. During the experiment mean air temperature and CO2 concentration ranged from 26.96 ± 0.98ºC and 537.86 ± 18.36 ppmv in the control to 31.75 ± 0.50ºC and 1636.96 ± 17.99 ppmv in the extreme chamber, respectively. However, phosphorus concentration in the leaf litter decreased with warming and elevated CO2. Leaf quality (percentage of carbon, nitrogen, phosphorus, cellulose and lignin) was not influenced by soil flooding. Fungal biomass and microbial leaf breakdown were positively influenced by temperature and CO2 increase and reached their highest values in the intermediate condition. Both total and shredder leaf breakdown, and shredder survival rate were similar among all climatic conditions. Thus, low leaf-litter quality due to climate change and higher leaf breakdown under intermediate conditions may indicate an increase of riparian metabolism due to temperature and CO2 increase, highlighting the risk (e.g., decreased productivity) of global warming for tropical streams. © 2017 Martins et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Carbon; Carbon Dioxide; Cellulose; Lignin; Nitrogen; Phosphorus; Carbon Dioxide; Water; Abiotic Stress; Air Temperature; Amazonas; Aquatic Environment; Climate Change; Controlled Study; Decomposition; Electric Conductivity; Flooding; Fungal Biomass; Greenhouse Effect; Hevea; Hevea Spruceana; Larva; Leaf Litter; Nonhuman; Phylloicus Elektoros; Plant Metabolism; Riparian Species; Survival Rate; Trichoptera; Biomass; Ecosystem; Metabolism; Temperature; Biomass; Carbon Dioxide; Ecosystem; Temperature; Water